The Relationship Between Brand Images and E-Commerce Practice on Firm Performance in Indonesia - Gebrina, Alifya (2009)
These researches provide Indonesian e-commerce practice in Indonesia and brand image on firms’ performance. Methods of research use quantitative related on 250 respondents give contributions. This research framework use independent variables (brand image and e-commerce practice) and dependent variable (firm performance). The finding result has positive significant relationship between independent variable to dependent variable. However, this research cannot be generalize and applicable on e-commerce practice in Indonesia only. It is beneficial for future research to observe the relationship between brand image and e-commerce practice on firm performance in other cou